The prognostic value of portal vein and hepatic artery involvement in patients with perihilar cholangiocarcinoma. Issue 1 (January 2018) - van Vugt, Jeroen L.A.; Gaspersz, Marcia P.; Coelen, Robert J.S.; Vugts, Jaynee; Labeur, Tim A.; de Jonge, Jeroen; Polak, Wojciech G.; Busch, Olivier R.C.; Besselink, Marc G.; IJzermans, Jan N.M.; Nio, Chung Y.; van Gulik, Thomas M.; et al.
Abstract: Background: Although several classifications of perihilar cholangiocarcinoma (PHC) include vascular involvement, its prognostic value has not been investigated. Our aim was to assess the prognostic value of unilateral and main/bilateral involvement of the portal vein (PV) and hepatic artery (HA) on imaging in patients with PHC. Methods: All patients with PHC between 2002 and 2014 were included regardless of stage or management. Vascular involvement was defined as apparent tumor contact of at least 180° to the PV or HA on imaging. Kaplan–Meier method with log-rank test was used to compare overall survival (OS) between groups. Cox regression was used for multivariable analysis. Results: In total, 674 patients were included with a median OS of 12.2 (95% CI 10.6–13.7) months. Patients with unilateral PV involvement had a median OS of 13.3 (11.0–15.7) months, compared with 14.7 (11.7–17.6) in patients without PV involvement ( p  = 0.12). Patients with main/bilateral PV involvement had an inferior median OS of 8.0 (5.4–10.7, p  < 0.001) months. Median OS for patients with unilateral HA involvement was 10.6 (9.3–12.0) months compared with 16.9 (13.2–20.5) in patients without HA involvement ( p  < 0.001). Patients with main/bilateral HA involvement had an inferior median OS of 6.9 (3.3–10.5, p  < 0.001). Independent poor prognostic factors included unilateral and main/bilateral HA involvement, but not PV involvement. Conclusion: Both unilateral and main HA involvement are independent poor prognostic factors for OS in patients presenting with PHC, whereas PV involvement is not.